Anti-noise ring magnet and Anti-
By managing the surface roughness and coercivity on the segmentation surface of Fe-based nanocrystalline alloy, and combining polishing and resin impregnation technology, excellent anti-noise ring magnets were prepared, which solved the difficulty of segmentation rings of Fe-based nanocrystalline alloys. The problem of magnets has achieved efficient noise reduction.
Patent Information
- Application Number
- CN202280098270.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-07-27
AI Technical Summary
It is difficult to produce a segmented annular magnet for anti-noise of Fe-based nanocrystalline alloy, and its shape is limited during molding, which is prone to defects and difficult to deal with, resulting in the inability to obtain sufficient noise reduction effect.
The surface roughness of the partition surface and the coercive force of the partition sheet are managed in such a way that the flatness of the partition surface and the coercive force of the partition sheet are 7.0 μm·A/m or less, and combined with polishing treatment and resin impregnation technology, the surface roughness of the partition surface and the coercive force of the partition sheet are managed in a manner that the surface roughness of the partition surface and the coercive force of the partition sheet are less than 7.0 μm·A/m, and the surface roughness of the partition sheet is prepared. Excellent anti-noise ring magnet.
The excellent noise reduction effect is achieved with an impedance relative magnetic permeability μrz at a frequency of 100 kHz or above, and the problem is solved that it is difficult to make a segmented annular magnet for Fe-based nanocrystalline alloy.
Smart Images

Figure CN119487589A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an anti-noise ring magnet and an anti-noise member. Background Art
[0002] Conventionally, there is known an anti-noise member including an annular magnet and a core case housing the annular magnet, in order to reduce noise current conducted in a cable connected to an electronic device.
[0003] Patent Document 1 describes a split ferrite core structure that can split a circular ferrite core into semicircular shapes and directly clamp a power cable. Such a split anti-noise component can be installed with the cable connected, compared to a non-split ferrite core that does not split the circular ferrite core, so it is more convenient.
[0004] Patent Document 2 describes a magnetic core formed by winding a Fe-based nanocrystalline alloy ribbon and a method for manufacturing the same. A non-dividable annular magnet using a Fe-based nanocrystalline alloy has excellent impedance characteristics in a wide frequency band compared to a ferrite core, and thus has a large noise reduction effect.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent document 1: Japanese Patent No. 2992269.
[0008] Patent document 2: Japanese Patent No. 6137408. Summary of the invention
[0009] Problem that the invention aims to solve
[0010] However, since Fe-based nanocrystalline alloys are formed using highly brittle metal strips as layers, defects are easily formed and the shape during molding is limited. Therefore, there is no split-type anti-noise ring magnet using nanocrystalline alloys. Therefore, nanocrystalline alloy cores cannot be used as easily as split-type ferrite cores.
[0011] Therefore, an object of the present invention is to provide a split-type anti-noise ring magnet which is difficult to produce using an Fe-based nanocrystalline alloy and which can achieve an excellent noise reduction effect.
[0012] Solutions for solving problems
[0013] The gist of the present invention is as follows.
[0014] [1] A ring-shaped magnet for noise suppression, with a cable inserted inside it.
[0015] The anti-noise annular magnet comprises soft magnetic metal thin strips stacked in radial direction.
[0016] The anti-noise annular magnet is composed of a plurality of non-annularly divided pieces, and the divided surfaces of the divided pieces are abutted against each other to form an annular shape for use.
[0017] The product FL×Hc of the flatness FL of the split surface and the coercive force Hc of the split piece is 7.0 μm·A / m or less,
[0018] The flatness FL is the sum of the absolute values of the maximum value and the minimum value of the cross-sectional curve measured in accordance with JIS B 0601:2001.
[0019] [2] The anti-noise annular magnet according to [1], wherein the arithmetic mean roughness Ra and the maximum height roughness Rz of the divided surface satisfy Ra≤0.7 μm and Rz≤10 μm, respectively.
[0020] [3] The anti-noise ring magnet according to [1] or [2] above, wherein the ring compression strength is 50 MPa or more.
[0021] [4] The anti-noise annular magnet according to any one of [1] to [3], wherein the impedance relative magnetic permeability μrz at a frequency of 100 kHz is 6000 or more.
[0022] [5] The anti-noise ring magnet according to any one of [1] to [4] above, wherein the soft magnetic metal strip contains an Fe-based nanocrystalline alloy.
[0023] [6] A noise-suppressing member comprising: the noise-suppressing annular magnet according to any one of [1] to [5] above; and
[0024] A split type magnetic core shell, which is formed by connecting subshells in a cylindrical shape in a manner that can be opened and closed, wherein the subshells are shaped by dividing the cylinder in a non-annular manner, and each of the split pieces of the anti-noise annular magnet is accommodated in the subshells.
[0025] When the split core case is closed, the split surfaces of the split pieces abut against each other inside the split core case to form the anti-noise annular magnet, and the surface pressure applied to the split surfaces is 0.05 MPa or more.
[0026] Effects of the Invention
[0027] According to the present invention, a split-type anti-noise ring magnet which is difficult to produce using an Fe-based nanocrystalline alloy can be provided, and an excellent noise reduction effect can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a top view of an example of an anti-noise ring magnet.
[0029] Figure 2 This is a perspective view of an example of an anti-noise ring magnet.
[0030] Figure 3 It is a diagram showing an example of an anti-noise member.
[0031] Figure 4 This is a diagram showing an example of a state in which the anti-noise member is opened.
[0032] Figure 5 This is a diagram showing an example of a state in which the anti-noise member is closed.
[0033] Figure 6 This is a diagram for explaining a method for measuring the pressing ring strength of a ring magnet for counteracting noise.
[0034] Figure 7 The diagram is for explaining the measurement method of flatness, arithmetic mean roughness Ra, and maximum height roughness Rz.
[0035] Figure 8 It is a diagram for explaining the measurement positions of flatness, arithmetic mean roughness Ra, and maximum height roughness Rz. DETAILED DESCRIPTION
[0036] The present invention will be described in detail below. In addition, in the present specification, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0037] [Anti-noise ring magnet]
[0038] The present invention is a ring-shaped magnet for noise reduction, in which a cable is inserted inside.
[0039] The anti-noise annular magnet comprises soft magnetic metal thin strips stacked in radial direction.
[0040] The anti-noise annular magnet is composed of a plurality of non-annularly divided pieces, and the divided surfaces of the divided pieces are abutted against each other to form an annular shape for use.
[0041] A product FL×Hc of the flatness FL of the split surface and the coercive force Hc of the split piece is 7.0 μm·A / m or less.
[0042] The flatness FL is the sum of the absolute values of the maximum and minimum values of the cross-sectional curve measured in accordance with JIS B 0601:2001.
[0043] Figure 1 A plan view of a noise-suppressing ring magnet 100 according to an embodiment of the present invention is shown. Figure 2 The following are three-dimensional views of an anti-noise annular magnet 100 according to an embodiment of the present invention. As shown in these figures, the anti-noise annular magnet 100 has an annular overall shape and includes thin soft magnetic metal strips stacked in radial directions. The anti-noise annular magnet 100 is composed of a plurality of split pieces 1a and 1b that are non-annularly split. Figure 1 and Figure 2 In the example of FIG. 1 , the anti-noise annular magnet 100 having an overall annular shape is divided into halves along the central axis direction. Figure 1 and Figure 2 As shown, the divided surfaces of the plurality of divided pieces 1a and 1b are brought into contact with each other to form a ring shape, and the cable is inserted into the hollow portion 11 partitioned by the anti-noise annular magnet 100 for use.
[0044] Fe-based nanocrystalline alloys are laminated bodies of soft magnetic thin strip metals with high brittleness, so there are limitations on the shape during molding, easy to be damaged, and difficult to handle. Therefore, it is difficult to provide a split type anti-noise annular magnet 100 using Fe-based nanocrystalline alloys. Even if a split type anti-noise annular magnet 100 is made using Fe-based nanocrystalline alloys, the management of the split surface becomes insufficient due to its high brittleness, so a sufficient noise reduction effect cannot be obtained.
[0045] The inventors of the present invention independently conducted intensive studies repeatedly and found that by managing the surface roughness of the split surface and the coercive force of the split pieces in such a way that the product FL×Hc of the flatness FL of the split surface and the coercive force Hc of the split pieces 1a and 1b is 7.0μm·A / m or less, it is possible to obtain an excellent noise reduction effect of 6000 or more at a frequency of 100kHz relative to the impedance permeability μrz, and thus invented the present anti-noise annular magnet 100. In order to obtain a more excellent noise reduction effect, the product FL×Hc of the flatness FL of the split surface and the coercive force Hc of the split pieces 1a and 1b is preferably 6.5μm·A / m or less, and more preferably 2.0μm·A / m or less. The lower limit of the product FL×Hc of the flatness FL of the split surface and the coercive force Hc of the split pieces is not particularly limited, but is preferably 0.005μm·A / m or more in accordance with the relationship with the lower limit values of the flatness and coercive force described later.
[0046] Here, "flatness" means the sum of the absolute values of the maximum and minimum values of the cross-sectional curve of the split surface measured in accordance with JIS B 0601:2001. However, when the maximum value of the cross-sectional curve includes a noise peak, the maximum peak height Rp of the roughness curve is taken as the maximum value. In addition, when the minimum value of the cross-sectional curve includes a noise peak, the peak value is not included in the calculation of flatness. For each split surface of the split pieces 1a and 1b (at Figure 1 , Figure 2 In the example of 4 surfaces in total), a SURFCOM 1400G surface roughness measuring instrument manufactured by Tokyo Seimitsu Co., Ltd. was used to measure the cross-sectional curve along the stacking direction of the soft magnetic metal strips (the direction that crosses the stacked body of the soft magnetic metal strips, the radial direction of the anti-noise annular magnet 100). Figure 7 , Figure 8 , the details of the measurement location are described. Figure 7 As shown, for the plurality of divided surfaces 10a and 10a' of each divided piece 1a, at least three positions, namely, the upper portion R1, R1', the middle portion R2, R2', and the lower portion R3, R3', are measured for each divided surface. Figure 8 The dividing surface 10a is 50 mm in area, with the width of the soft magnetic metal strip (equivalent to the height of the anti-noise ring magnet 100 in the central axis direction) L = 10 mm and the length of the soft magnetic metal strip in the stacking direction (equivalent to the thickness of half the difference between the inner and outer diameters of the anti-noise ring magnet 100) e = 5 mm. 2 The measurement position of the flatness in the case of Figure 8As shown, when the width L of the soft magnetic metal strip at the dividing surface 10a is 3mm<L<15mm, profile curves are measured at a total of three positions: (1) the upper portion R1 close to the inner side and at the end of the width L direction of the soft magnetic metal strip at the dividing surface 10a where w1=1mm; (2) the central portion R2 of the width L direction of the soft magnetic metal strip at the dividing surface 10a (the distance w2 from R1 and R3 is equal); and (3) the lower portion R3 close to the inner side and at the end of the other side of the width L of the soft magnetic metal strip at the dividing surface 10a where w1=1mm, and the flatness is determined based on the profile curves. As an exception, when the width L of the soft magnetic metal strip is 2 mm < L ≤ 3 mm, the cross-sectional curve is measured at two positions, namely, upper R1, R1', which is 1 mm away from the end in the direction of the width L and closer to the inside, and lower R3, R3', which is 1 mm away from the other end in the direction of the width L and closer to the inside. When L = 2 mm, the cross-sectional curve is measured at one position on the center line of the width of the soft magnetic metal strip. When the width L of the soft magnetic metal strip is 15 mm or more, one measurement position is added every 5 mm. Next, the measurement length of the cross-sectional curve is described. According to JIS B 0601: 2001, the measurement length y1 of the soft magnetic metal strip in the stacking direction of the dividing surface 10a is 4 mm. The cross-sectional curve is measured at the center of the length e of the soft magnetic metal strip in the stacking direction of the dividing surface 10a. When the length e of the soft magnetic metal strip in the stacking direction of the dividing surface 10a is 8 mm or more, one measurement position is added every 4 mm. In the case where it is not possible to increase a measurement position every 4 mm, measure 4 mm of the central part of the length e in the stacking direction. In addition, when the dividing surface is not a straight line but a curve, or has a step difference, the length of the stacking direction of the soft magnetic metal strip is used as the measuring length, and the surface of the soft magnetic metal strip is not included in the measuring position. In the case where the anti-noise annular magnet 100 is composed of two dividing pieces 1a and 1b, the average value of the sum of the absolute values of the maximum and minimum values of the cross-sectional curve at a total of 12 positions is used as the flatness of the dividing surfaces 10a and 10b. In addition, the size of the dividing surface 10a of the anti-noise annular magnet 100 is measured by the same method as the size measurement method of the anti-noise annular magnet 100 described later.
[0047] In the present invention, the flatness of the divided surfaces 10a and 10b obtained after polishing can be adjusted by polishing the cut surface. The flatness can be adjusted by the mesh number of the polishing cloth paper used for polishing, etc. As described later, when a protective layer such as a rust preventive or a film sheet is added to the divided surfaces 10a and 10b, the flatness of the divided surfaces 10a and 10b is measured after the protective layer is added.
[0048] The coercive force of the split pieces 1a and 1b is the average value of the measured values measured three times using an automatic coercive force meter K-HC1000 made by Tokyo Special Steel. During the measurement, the split pieces 1a and 1b are placed in a state where the split surfaces are mutually abutted in a ring shape, and the coercive force is measured. The coercive force of the split pieces 1a and 1b can be adjusted by the material properties of the soft magnetic metal strip, the temperature and time of the heat treatment of the soft magnetic metal strip, the splitting (cutting) method of the anti-noise annular magnet 100, and the polishing processing conditions of the cut surface.
[0049] The flatness FL is not particularly limited as long as it is adjusted so that the product FL×Hc of the flatness FL of the split surfaces 10a and 10b and the coercive force Hc of the split piece is 7.0 μm·A / m or less. The flatness is preferably 1.5 μm or less, and more preferably 0.7 μm or less. The lower limit of the flatness is not particularly limited, but from the perspective of mass productivity of machining, it is preferably 0.05 μm or more.
[0050] The coercive force Hc is not particularly limited as long as it is adjusted in such a way that the product FL×Hc of the flatness FL of the split surfaces 10a and 10b and the coercive force Hc of the split piece is 7.0 μm·A / m or less. The coercive force Hc is preferably 7.0 A / m or less, and more preferably 5.0 A / m or less. The lower limit of the coercive force is not particularly limited, but because the value of the coercive force varies depending on the material properties of the soft magnetic metal strip and the polishing conditions of the cut surface, it is preferably 0.1 A / m or more.
[0051] The anti-noise annular magnet 100 is composed of a plurality of split pieces 1a and 1b that are split in a non-annular manner. The number and size of the split pieces that constitute the anti-noise annular magnet 100 are not particularly limited. Figure 1 , Figure 2As shown, the anti-noise annular magnet 100 can be composed of two split pieces 1a and 1b, or it can be composed of more split pieces. In addition, as long as the overall shape of the split pieces 1a and 1b of the anti-noise annular magnet 100 is non-annular, it can also be divided into any shape. In one example, the anti-noise annular magnet 100 is divided in a manner parallel to the central axis direction. In addition, the central axis direction here refers to the direction on a straight line extending perpendicularly to the radial direction from the center of the anti-noise annular magnet 100. For example, each split piece 1a and 1b can be a shape in which the anti-noise annular magnet 100 is divided radially. According to this structure, even when the cable is connected to an electronic device, an electronic component, etc., the anti-noise annular magnet 100 can be interspersed with the cable, so it is easy to install the anti-noise annular magnet 100 on the cable. Alternatively, after the plurality of split pieces 1a and 1b are brought into contact with each other, the split pieces 1a and 1b may be bonded to each other so as to be immobile therebetween, or the split pieces 1a and 1b may be fixed to each other using a split core case or a tape described later.
[0052] The soft magnetic metal strip constituting the anti-noise annular magnet 100 is not particularly limited. In order to obtain an excellent noise reduction effect, a soft magnetic material with a small coercive force and a large impedance relative permeability is preferred. In order to obtain a particularly excellent noise reduction effect, the impedance relative permeability μrz of the soft magnetic metal strip constituting the anti-noise annular magnet 100 at a frequency of 100kHz is more preferably 6000 or more, and further preferably 12000 or more. In addition, in order to obtain a particularly excellent noise reduction effect, the coercive force of the soft magnetic metal strip constituting the anti-noise annular magnet 100 is preferably 7.0 A / m or less.
[0053] As soft magnetic materials, ferrites such as Mn-Zn ferrite, Ni-Zn ferrite, and Ni-Zn-Cu ferrite; soft magnetic metals such as Fe-Ni alloys (Permalloy) and Fe-Si alloys (silicon steel); amorphous alloys such as Co-based amorphous alloys and Fe-based amorphous alloys; and Fe-based nanocrystalline alloys can be used.
[0054] The soft magnetic metal strip constituting the anti-noise annular magnet 100 is preferably an Fe-based nanocrystalline alloy. When the soft magnetic metal strip constituting the anti-noise annular magnet 100 is an Fe-based nanocrystalline alloy, for example, it is particularly preferred to have (Fe 1-a M a ) 100-x-y-z-b-c-d A x M' y M” z X b Si c B d(atomic %) (wherein, M represents at least one element selected from Co and Ni, A represents at least one element selected from Cu and Au, M' represents at least one element selected from Ti, V, Zr, Nb, Mo, Hf, Ta and W, M" represents at least one element selected from Cr, Mn, Sn, Zn, Ag, In, platinum group elements, Mg, N and S, X represents at least one element selected from C, Ge, Ga, Al and P, a, x, y, z, b, c and d are respectively A number that satisfies 0≤a≤0.1, 0.1≤x≤3, 1≤y≤10, 0≤z≤10, 0≤b≤10, 11≤c≤17, 3≤d≤10. ) is an Fe-based nanocrystalline alloy of the general formula. In addition, the composition of the Fe-based nanocrystalline alloy is not particularly limited, and preferably, in terms of atomic %, Cu: 0.5-2.0%, Nb: 1.0-5.0%, Si: 11.0-15.0%, B: 5.0-10.0%, and the remainder is a component composition substantially consisting of Fe.
[0055] In order to obtain the noise reduction effect, the arithmetic mean roughness Ra of the dividing surfaces 10a and 10b is preferably Ra≤0.7μm, and more preferably Ra≤0.35μm. In addition, the lower limit of the arithmetic mean roughness Ra of the dividing surfaces 10a and 10b is not particularly limited. The arithmetic mean roughness Ra of the dividing surfaces 10a and 10b can be adjusted by polishing the cut surface. The arithmetic mean roughness Ra of the dividing surfaces 10a and 10b can be adjusted by the mesh size of the polishing cloth paper used for polishing, the mesh size of the abrasive grains in the polishing suspension (liquid in which the abrasive grains for polishing are suspended), and the material of the abrasive grains.
[0056] In order to obtain an excellent noise reduction effect, the maximum height roughness Rz of the dividing surfaces 10a and 10b is preferably Rz≤10μm, and more preferably Rz≤5μm. The lower limit of the maximum height roughness Rz of the dividing surfaces 10a and 10b is not particularly limited. The maximum height roughness Rz of the dividing surfaces 10a and 10b can be adjusted by polishing the dividing surfaces 10a and 10b. The maximum height roughness Rz of the dividing surfaces 10a and 10b can be adjusted by the mesh number of the polishing cloth paper used for polishing, the mesh number of the abrasive grains in the polishing suspension, and the material of the abrasive grains.
[0057] Here, the arithmetic mean roughness Ra and the maximum height roughness Rz of the divided surfaces 10a and 10b were measured using a SURFCOM 1400G surface roughness measuring instrument manufactured by Tokyo Seimitsu Co., Ltd. on each divided surface of the divided pieces 1a and 1b (at Figure 1 , Figure 2The measurement positions of at least three positions of each of the four surfaces (in the example of the embodiment of the present invention) are measured, and the average values of at least 12 positions in total are used as the arithmetic mean roughness Ra and the maximum height roughness Rz of the divided surfaces 10a and 10b. The measurement positions of the arithmetic mean roughness Ra and the maximum height roughness Rz are the same as the measurement positions of the above-mentioned flatness.
[0058] The compression ring strength of the anti-noise annular magnet 100 is preferably 50 MPa or more. Because the compression ring strength of the anti-noise annular magnet 100 is 50 MPa or more, it is easy to handle when polishing the split surfaces 10a and 10b. In addition, it is possible to apply appropriate surface pressure to the split surfaces of the split pieces 1a and 1b so that they abut against each other. Based on the reasons that it is easy to perform polishing and truncation processing and easy to maintain the shape, the compression ring strength of the anti-noise annular magnet 100 is more preferably 70 MPa or more. The upper limit of the compression ring strength of the anti-noise annular magnet 100 is not particularly limited, and can be 800 MPa or less.
[0059] The compression ring strength is measured as follows. Figure 6 As shown, the ring magnet 100 for noise suppression is fixed with a fixture 5 that matches the diameter of the ring magnet 100 so that the split surfaces 10a and 10b of the split pieces 1a and 1b of the ring magnet 100 for noise suppression abut against each other, and the ring strength is measured using Autograph AGX-20kNBVD manufactured by Shimadzu Corporation while being compressed in a direction perpendicular to the split surfaces 10a and 10b. The maximum load that causes cracks is set to F, and the ring strength K is calculated as F (De) / Le 2 Here, if Figure 2 As shown, D, L, and e are the outer diameter D, height L, and half thickness e of the difference between inner and outer diameters (difference between outer diameter D and inner diameter d) of the anti-noise ring magnet 100, respectively. The dimensions of the anti-noise ring magnet 100 are measured by the method described below.
[0060] The compression ring strength of the anti-noise ring magnet 100 can be adjusted by the type of soft magnetic metal thin strip constituting the anti-noise ring magnet 100, and can also be adjusted by coating the anti-noise ring magnet 100 with resin or wrapping an insulating tape around it. The anti-noise ring magnet 100 can also be impregnated with resin to improve the compression ring strength. As the resin coating agent or the resin impregnating agent, epoxy resin, acrylic resin, or a mixture thereof is preferred.
[0061] The impedance relative magnetic permeability μrz of the anti-noise annular magnet 100 at a frequency of 100 kHz is preferably 6000 or more, more preferably 8000 or more, and further preferably 12000 or more. The upper limit of the impedance relative magnetic permeability μrz of the anti-noise annular magnet 100 at a frequency of 100 kHz is not particularly limited.
[0062] The impedance relative magnetic permeability μrz of the existing split ferrite core at a frequency of 100kHz is about 4000. In contrast, in the anti-noise annular magnet 100 of the present invention, an impedance relative magnetic permeability μrz of about 1.5 times the existing one can be obtained: 6000 or more, and more preferably about 2.0 times the impedance relative magnetic permeability μrz of the existing split ferrite core: 8000 or more. In the anti-noise annular magnet 100 of the present invention, the noise suppression effect is much greater than that of the existing split ferrite core, which is related to the miniaturization and lightweight of the anti-noise annular magnet 100. The cables of electronic components, power generation devices, power supply devices, communication equipment, etc. in automobiles are wired in narrow spaces. In addition, since electronic equipment such as inverters and converters in industrial machinery have also been miniaturized in recent years, there are many cases of wiring in narrow spaces. In order to obtain excellent noise reduction effect in the existing split ferrite core, it is necessary to increase the number of cable windings to improve the noise reduction effect, or increase the volume occupied by the magnetic material. In contrast, in the anti-noise annular magnet 100 of the present invention, since it can achieve a noise suppression effect far greater than that of the existing split ferrite core, and can be miniaturized and lightweight, it can be installed in cables of electronic components, power generation devices, power supply devices, communication equipment, etc. in automobiles, and cables of electronic equipment such as inverters and converters in industrial machinery, and is particularly effective as an anti-noise annular magnet 100 for suppressing noise generated inside or outside these electronic components and electronic equipment and conducted in the cables.
[0063] The impedance relative permeability at a frequency of 100 kHz was measured as follows. In the measurement of the impedance relative permeability, a 4294A impedance analyzer manufactured by Keysight Corporation was used. A 0.5 mm single-wire lead wire (H-PVC manufactured by Tanaka Electric Wire) was passed through the anti-noise annular magnet 100 once, and a lead wire fixture (16047E manufactured by Keysight Corporation) was used to set the surface pressure applied to the split surfaces 10a and 10b to 0.1 MPa for measurement.
[0064] The overall shape of the anti-noise annular magnet 100 is not particularly limited as long as it is annular. Figure 1In addition to the right cylindrical shape (the outer shape of the section perpendicular to the central axis direction is a right circular ring shape) as shown in the figure, it can also be, for example, an elliptical cylindrical shape (the shape of the section perpendicular to the central axis direction is an elliptical ring shape), a square cylindrical shape (the shape of the section perpendicular to the central axis direction is a square ring shape), and a rounded square cylindrical shape (the shape of the section perpendicular to the central axis direction is a rounded square ring shape). The shape of the split pieces 1a and 1b is determined according to the overall shape of the anti-noise annular magnet 100 and the way of splitting. For example, the overall shape of the anti-noise annular magnet 100 is a right cylindrical shape or an elliptical cylindrical shape, and when the anti-noise annular magnet 100 is symmetrically divided in half along the central axis direction, the shape of the split pieces 1a and 1b can be arc-shaped. The overall shape of the anti-noise annular magnet 100 is a rounded square tube, and when the anti-noise annular magnet 100 is divided into two halves symmetrically along the central axis direction, the shapes of the split pieces 1a and 1b can be "コ"-shaped, U-shaped, or linear according to the overall shape of the anti-noise annular magnet 100.
[0065] In addition, when the overall shape of the anti-noise annular magnet 100 is not annular, Figure 6 The clamp 5 is changed to a shape corresponding to the shape of the side surface of the anti-noise annular magnet 100, and the compression ring strength is measured. In addition, when the anti-noise annular magnet 100 includes three or more split pieces, the compression ring strength when the anti-noise annular magnet 100 is split in half symmetrically along the central axis direction is obtained as the compression ring strength of the anti-noise annular magnet 100.
[0066] The size of the anti-noise annular magnet 100 is not particularly limited and can be set according to the purpose. In one example, the outer diameter D of the anti-noise annular magnet 100 can be greater than 10 mm, and can also be less than 300 mm. In one example, the inner diameter d of the anti-noise annular magnet 100 can be greater than 2 mm, and can also be less than 200 mm. The height L of the anti-noise annular magnet 100 in the central axis direction can be greater than 2 mm, and can also be less than 100 mm. In addition, in the case where the anti-noise annular magnet 100 is not a perfect circular ring, the outer diameter D and the inner diameter d are respectively equivalent to the outer diameter of the circle and the inner diameter of the circle. The average value of three measurements measured using a vernier caliper, a micrometer, and a microscope image is obtained as the size of the anti-noise annular magnet 100.
[0067] exist Figure 1 , Figure 2In the figure, the example of a linear type in which the dividing surfaces 10a and 10b of the dividing pieces 1a and 1b are parallel to the stacking direction of the soft magnetic metal strip is shown, but the shape of the dividing surfaces 10a and 10b of the dividing pieces 1a and 1b is not particularly limited. The shape of the dividing surfaces 10a and 10b of the dividing pieces 1a and 1b can also be, for example, an inclined type, that is, the dividing surfaces 10a and 10b intersect with the stacking direction of the soft magnetic metal strip and are not parallel to the stacking direction of the soft magnetic metal strip. In addition, the dividing surfaces 10a and 10b can also be a shape that intersects with the central axis direction of the anti-noise annular magnet 100 and is not parallel to the central axis direction of the anti-noise annular magnet 100. In addition, the shape of the dividing surfaces 10a and 10b of the dividing pieces 1a and 1b is not limited to a plane. That is, the shape of the dividing surfaces 10a and 10b of the dividing pieces 1a and 1b is not limited to a straight line at the starting point and the end point of the division, and does not depend on the division path. When the dividing surfaces 10a and 10b are curved or have a step difference, the length of the soft magnetic metal strip in the stacking direction is used as the measurement length of the flatness, arithmetic mean roughness Ra and maximum height roughness Rz, and the stacking surface of the soft magnetic metal strip is not included in the measurement position.
[0068] The split surfaces 10a and 10b may also have a protective film formed by a rust preventive or a thin film sheet. In addition, the side surface (split side surface) continuous with the outer periphery of the split surfaces 10a and 10b of the anti-noise annular magnet 100 may also be protected by resin coating or tape. The outer periphery (end) of the split surfaces 10a and 10b may also be chamfered.
[0069] Preferably, the anti-noise annular magnet 100 is used by pressing with an appropriate load in such a manner that the surface pressure applied to the split surfaces 10a and 10b is 0.05MPa or more when the split surfaces 10a and 10b of the split pieces 1a and 1b are brought into contact with each other. In the existing split-type ferrite core, the surface pressure applied to the split surfaces 10a and 10b is about 0.025MPa. However, in the case of making the split-type anti-noise annular magnet 100 using the Fe-based nanocrystalline alloy as described above, the management of the split surfaces 10a and 10b is prone to become insufficient due to its high brittleness. Therefore, in addition to adjusting the surface roughness of the split surfaces 10a and 10b as described above, it can also be used by pressing with an appropriate load of 0.05MPa or more applied to the split surfaces 10a and 10b, thereby obtaining a particularly excellent noise reduction effect. The surface pressure applied to the split surfaces 10a and 10b is more preferably 0.10MPa or more. The upper limit of the surface pressure applied to the divided surfaces 10a and 10b is not particularly limited, but is preferably 5.0 MPa or less in order to prevent deformation and damage of the divided surfaces 10a and 10b due to excessive load.
[0070] The surface pressure applied to the divided surfaces 10a and 10b of the divided pieces 1a and 1b was measured as follows: A pressure measuring film manufactured by Fujifilm Corporation was sandwiched between the divided surfaces 10a and 10b of the divided pieces 1a and 1b, and the surface pressure was measured for two minutes while they were in contact.
[0071] When the split surfaces 10a and 10b of the split pieces 1a and 1b of the anti-noise annular magnet 100 are brought into contact with each other in such a manner that the surface pressure applied to the split surfaces 10a and 10b is 0.05 MPa or more, for example, a tape or the like is wound around the outer periphery of the anti-noise annular magnet 100 in such a state that the split surfaces 10a and 10b of the split pieces 1a and 1b of the anti-noise annular magnet 100 are brought into contact with each other. Alternatively, the anti-noise annular magnet 100 is housed in a split core housing, which is formed by connecting sub-housings in a cylindrical shape in an openable and closable manner, wherein the sub-housings are shaped by dividing the cylinder non-annularly, and in the split core housing, the surface pressure applied to the split surfaces 10a and 10b can be adjusted to be 0.05 MPa or more for use. Hereinafter, an anti-noise component having the above-mentioned anti-noise annular magnet 100 will be described.
[0072] [Noise-proof components]
[0073] An anti-noise member according to one embodiment includes:
[0074] Ring magnets for noise suppression; and
[0075] A split type magnetic core shell, which is formed by connecting subshells in a cylindrical shape in a manner that can be opened and closed, wherein the subshells are shaped by dividing the cylinder in a non-annular manner, and each of the split pieces of the anti-noise annular magnet is accommodated in the subshells.
[0076] When the split core case is closed, the split surfaces of the split pieces abut against each other inside the split core case to form the anti-noise annular magnet, and the surface pressure applied to the split surfaces is 0.05 MPa or more.
[0077] use Figure 3 to Figure 5 , an anti-noise component according to one embodiment is described. Figure 3 to Figure 5 FIG. 1 is a diagram showing an example of a noise-proof component. Figure 3 to Figure 5As shown, the anti-noise component 200 has an anti-noise annular magnet 100 and a split core shell 60 that accommodates the anti-noise annular magnet 100. The split core shell 60 is composed of sub-shells 6a and 6b connected into a cylindrical shape by a hinge portion or the like so as to be able to open and close, wherein the sub-shells are shaped in a non-annular manner. In one example, the split core shell 60 is composed of sub-shells 6a and 6b connected into a cylindrical shape by a hinge portion or the like so as to be able to open and close, wherein the sub-shells are shaped in a manner in which the cylinder is divided parallel to the center axis direction. Figure 3 to Figure 5 In the example, the sub-shells 6a and 6b are shown in a manner of dividing the cylinder in half along the central axis direction, but the number and manner of the sub-shells 6a and 6b constituting the split core shell 60 are not particularly limited. Each sub-shell 6a and 6b contains a split piece 1a and 1b of the anti-noise annular magnet 100.
[0078] like Figure 3 to Figure 5 As shown in the example, the sub-shells 6a and 6b may also be composed of a dual structure of an inner shell 3 and an outer shell 4. The inner shell 3 has an inner wall portion that protects the inner peripheral hole of the anti-noise annular magnet 100. The outer shell 4 has: an outer wall portion that protects the outer peripheral portion of the anti-noise annular magnet 100; a bottom plate portion that protects the bottom portion; and an upper plate portion that has the function of protecting the upper surface portion. Moreover, the sub-shells 6a and 6b can be connected by a hinge portion. Figure 3 to Figure 5 In the example, each split piece 1a, 1b is fixed to the inner housing 3 with a double-sided adhesive tape 2 of acrylic foam having cushioning properties. The inner housing 3 is inserted into the outer housing 4. The split surfaces 10a, 10b of the split pieces 1a, 1b are exposed and the outer housing is opened as the open state before the cable is installed.
[0079] When the split core housing 60 is closed, inside the split core housing 60, the split surfaces 10a and 10b of the split pieces 1a and 1b abut against each other to form the above-mentioned annular anti-noise annular magnet 100. At this time, the surface pressure applied to the split surfaces 10a and 10b is preferably 0.05MPa or more. As described above, a particularly excellent noise reduction effect can be obtained by pressing the split surfaces 10a and 10b with an appropriate load of 0.05MPa or more. When the split core housing 60 is closed, the surface pressure applied to the split surfaces 10a and 10b is more preferably 0.10MPa or more. When the split core housing 60 is closed, the upper limit of the surface pressure applied to the split surfaces 10a and 10b is not particularly limited, but in order to prevent deformation and damage of the split surfaces 10a and 10b caused by excessive load, it is preferably 5.0MPa or less.
[0080] When the split core case 60 is closed, the surface pressure applied to the split surfaces 10a and 10b of the split pieces 1a and 1b is measured as follows. The split core case 60 is folded in half with the hinge as the center and closed, and a pressure measuring film made by Fujifilm Corporation is sandwiched between the split surfaces 10a and 10b of the split pieces 1a and 1b and brought into contact with each other. The surface pressure measurement is continued for two minutes in the state where the split core case 60 is closed.
[0081] Since the core housing is a split core housing 60, it is easy to install and remove the cable, and the split core housing 60 can be installed and removed after the cable is connected. Therefore, even when using electronic equipment, the split core housing 60 can be installed and removed to adjust the noise attenuation.
[0082] The material of the split core housing 60 is not particularly limited. For example, polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyamide (PA), polyphenylene sulfide (PPS), silicone resin, silicone elastomer, etc. can be used. In addition, materials containing glass fiber (GF), carbon fiber (CF), graphite (GP), etc. to improve strength and heat resistance can also be used in the thermoplastic plastic.
[0083] [Manufacturing method]
[0084] The manufacturing method of the anti-noise annular magnet 100 of the present invention is not particularly limited. For example, a thin strip of amorphous alloy with a thickness of 5 to 50 μm is obtained from an alloy melt by a single-roll method, etc., the thin strip of amorphous alloy is wound into a cylindrical shape, and a heat treatment is performed at a temperature of 300°C to 700°C for 5 to 20 minutes to obtain an annular magnet composed of an Fe-based nanocrystalline alloy. The annular magnet is cut into a non-annular shape to obtain split pieces 1a and 1b. The cut surfaces of the split pieces 1a and 1b are polished using polishing cloth paper to obtain an anti-noise annular magnet 100 having split surfaces 10a and 10b with a specified surface roughness.
[0085] Before cutting the annular magnet, the anti-noise annular magnet 100 may be impregnated with resin to improve the compression ring strength. For example, the annular magnet is immersed in a solution obtained by mixing epoxy resin and curing agent in a specified amount ratio, evacuated to below 0.1MPa and maintained for about 15 minutes, and then opened to the atmosphere to allow the resin to be impregnated in the annular magnet. The annular magnet impregnated with resin is placed in the atmosphere at room temperature for about 24 hours to solidify. After the annular magnet impregnated with resin is cut into non-annular shapes according to the above method to obtain split pieces 1a and 1b, the cut surfaces of the split pieces 1a and 1b are polished with polishing cloth paper to obtain the anti-noise annular magnet 100 having split surfaces 10a and 10b with a specified surface roughness.
[0086] After the split surfaces 10a and 10b are polished, a protective film or the like may be formed on the split surfaces 10a and 10b by using a rust preventive or a film sheet or the like. The side surfaces (split side surfaces) that are continuous with the split surfaces 10a and 10b may also be protected by using a resin coating or an adhesive tape. In addition, the outer periphery (ends) of the split surfaces 10a and 10b may be chamfered.
[0087] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to these examples.
[0088] Example
[0089] (Examples 1_1 to 7)
[0090] Make as Figure 1 The anti-noise annular magnet shown in the figure. First, the alloy melt, which is composed of Cu: 1%, Nb: 3%, Si: 13.5%, B: 9% in atomic %, and the remainder is substantially composed of Fe, is quenched by a single-roll method to obtain a thin strip of Fe-based amorphous alloy with a width of 10 mm and a thickness of 20 μm. The Fe-based amorphous alloy is wound to form a cylindrical shape with an outer diameter of 28.5 mm, an inner diameter of 18.0 mm, and a height of 10 mm. The cylindrical Fe-based amorphous alloy is inserted into a heat treatment furnace maintained at 490°C in an argon environment and subjected to heat treatment for 10 minutes. Then, an annular magnet composed of an Fe-based nanocrystalline alloy is prepared. The obtained annular magnet is immersed in a solution obtained by mixing an epoxy resin and a curing agent in a specified quantitative ratio, and after evacuating below 0.1 MPa and maintaining for 15 minutes, it is opened to the atmosphere to allow the resin to be impregnated in the annular magnet. The annular magnet impregnated with resin is placed in the atmosphere at room temperature for 24 hours to solidify. The resin impregnated ring magnet is Figure 1The ring magnet is divided into two halves in the radial direction in the manner shown to form a semicircular shape. The cross-section of the ring magnet is polished starting from the polishing paper mesh number #400 and gradually decreasing the mesh number. The cross-section is polished to 0.5 μm aluminum oxide film in Example 1_1, to 1.0 μm aluminum oxide film in Example 1_2, to #2500 in Example 1_3, to #2000 in Example 1_4, and to #800 in Examples 1_5 to 7, to obtain an anti-noise ring magnet with a divided surface having a specified surface roughness.
[0091] The obtained anti-noise ring magnet was evaluated for impedance relative permeability, coercive force, surface roughness (flatness, Ra, Rz), surface pressure applied to the split surface, and ring pressing strength according to the above-mentioned method. The results are shown in Table 1.
[0092] (Examples 2_1 to 3)
[0093] For the anti-noise annular magnet made in the same manner as in Example 1_2, the surface pressure applied to the split surface of the split piece was changed, and the impedance relative permeability was measured according to the above method. The relationship between the obtained impedance relative permeability and the surface pressure is summarized in Table 2. With respect to the obtained contact area relative to the split surface of the anti-noise annular magnet, the colored portion above 0.05 MPa was processed as the effective cross-sectional area, and it was confirmed that the coloring rate was 50% or more.
[0094] (Examples 3_1 to 5)
[0095] In order to confirm the influence of the resin impregnated in the annular magnet on the impedance relative permeability, for the annular magnet produced in the same manner as in Example 1_2, in Examples 3_1 to 4, the impregnated resin is the same epoxy resin as in Example 1_2, and in Example 3_5, the impregnated resin is a one-component acrylic resin to produce an anti-noise annular magnet. In Examples 3_3 to 4, after impregnation with the resin, the anti-noise annular magnet is further immersed in the epoxy resin, the excess epoxy resin is wiped off, and the epoxy resin is left at room temperature for about 24 hours to solidify, and the surface of the anti-noise annular magnet is coated with the epoxy resin. After impregnation with the resin, or after further surface coating with the resin, an anti-noise annular magnet is produced under the same conditions as in Example 1_2. For the produced anti-noise annular magnet, the compression ring strength and the impedance relative permeability are calculated according to the above method. The results are shown in Table 3.
[0096] (Comparative Examples 1_1 to 7)
[0097] The split surface was polished differently. In Comparative Examples 1_1 to 2, the split surface was polished to #400, in Comparative Examples 1_3 to 4, the split surface was polished to #220, and in Comparative Example 1_7, the split surface was not polished. Except for this, the same method as in Example 1_1 was used to produce an anti-noise ring magnet. The impedance relative permeability, coercive force, surface roughness (flatness, Ra, Rz), surface pressure applied to the split surface, and pressure ring strength of the obtained anti-noise ring magnet were evaluated according to the above method. The results are shown in Table 1. In addition, Comparative Example 1_5 uses the existing Mn-Zn ferrite, and Comparative Example 1_6 uses the existing Ni-Zn ferrite. According to the above method, the impedance relative permeability, coercive force, surface roughness (flatness, Ra, Rz), surface pressure applied to the split surface, and pressure ring strength were evaluated. The results are shown in Table 1.
[0098] (Comparative Example 2_1-2)
[0099] For the anti-noise ring magnet produced under the same conditions as in Example 1_2, the surface pressure applied to the split surface of the split piece was changed, and the impedance relative permeability, coercive force, and flatness were measured according to the above method. The results are shown in Table 2.
[0100] (Comparative Examples 3_1 to 4)
[0101] Ring magnets were prepared under the same conditions as in Examples 1_1 to 5 except that polyester resin was used as the resin impregnation agent. The ring strength, impedance relative permeability, coercive force, and flatness of the ring magnets were measured according to the above method. The results are shown in Table 3.
[0102] [Table 1]
[0103]
[0104] [Table 2]
[0105]
[0106] [Table 3]
[0107]
[0108] As described above, by satisfying the conditions of the present invention, it is possible to produce an anti-noise member having an impedance relative magnetic permeability μrz of 6000 or more at a frequency of 100 kHz.
[0109] Industrial Applicability
[0110] The present anti-noise component is installed in cables of electronic components, power generation devices, power supply devices, communication equipment, and OA / FA equipment in automobiles, and is particularly effective as an anti-noise annular magnet for suppressing noise generated inside or outside these electronic components and electronic equipment and conducted in the cables.
[0111] Description of Reference Numerals
[0112] 1, 1a, 1b: split pieces;
[0113] 10, 10a, 10b: splitting surface;
[0114] 100: Ring magnet for noise reduction;
[0115] 200: Anti-noise components;
[0116] 2: Double-sided tape;
[0117] 3: Inner shell;
[0118] 4: Outer shell;
[0119] 5: fixture;
[0120] 6a, 6b: sub-shell;
[0121] 60: split core shell;
[0122] 11: Hollow part.
Claims
1. A ring-shaped magnet for noise suppression, which is used by inserting a cable inside. The anti-noise annular magnet comprises soft magnetic metal thin strips stacked in radial direction. The anti-noise annular magnet is composed of a plurality of non-annularly divided pieces, and the divided surfaces of the divided pieces are abutted against each other to form an annular shape for use. The product FL×Hc of the flatness FL of the split surface and the coercive force Hc of the split piece is 7.0 μm·A / m or less, The flatness FL is the sum of the absolute values of the maximum value and the minimum value of the cross-sectional curve measured in accordance with JIS B 0601:2001.
2. The anti-noise annular magnet according to claim 1, wherein: The arithmetic mean roughness Ra and the maximum height roughness Rz of the divided surface satisfy Ra≤0.7 μm and Rz≤10 μm, respectively.
3. The anti-noise annular magnet according to claim 1 or 2, wherein: The compression ring strength is above 50MPa.
4. The anti-noise annular magnet according to any one of claims 1 to 3, wherein: The impedance relative magnetic permeability μrz at a frequency of 100 kHz is 6000 or more.
5. The anti-noise annular magnet according to any one of claims 1 to 4, wherein: The soft magnetic metal ribbon comprises a Fe-based nanocrystalline alloy.
6. A noise-proof component, comprising: The anti-noise annular magnet according to any one of claims 1 to 5; and A split type magnetic core shell, which is formed by connecting subshells in a cylindrical shape in a manner that can be opened and closed, wherein the subshells are shaped by dividing the cylinder in a non-annular manner, and each of the split pieces of the anti-noise annular magnet is accommodated in the subshells. When the split core case is closed, the split surfaces of the split pieces abut against each other inside the split core case to form the anti-noise annular magnet, and the surface pressure applied to the split surfaces is 0.05 MPa or more.
Citation Information
Patent Citations
Plunger for transfer molding machine
JP1986037408A
Coil component
CN111627646A
Anti-noise member
CN113557580A
Annular magnetic body for noise control
WO2021157165A1